SARS-CoV-2 variants with NSP12 P323L/G671S mutations display enhanced virus replication in ferret upper airways and higher transmissibility - Kim, Se Mi; Kim, Eun Ha; Casel, Mark Anthony B.; Kim, Young Il; Sun, Rong; Kwak, Mi Jeong; Yoo, Ji Seung; Yu, Mina; Yu, Kwang Min; Jang, Seung Gyu; Rollon, Rare; Choi, Jeong Ho; et al. (Cell Reports, 2023)
With the emergence of multiple predominant SARS-CoV-2 variants, it becomes important to have a comprehensive assessment of their viral fitness and transmissibility. Here, we demonstrate that natural temperature differences between the upper (33°C) and lower (37°C) respiratory tract have profound effects on SARS-CoV-2 replication and transmissibility. Specifically, SARS-CoV-2 variants containing the NSP12 mutations P323L or P323L/G671S exhibit enhanced RNA-dependent RNA polymerase (RdRp) activity at 33°C compared with 37°C and high transmissibility. Molecular dynamics simulations and microscale thermophoresis demonstrate that the NSP12 P323L and P323L/G671S mutations stabilize the NSP12-NSP7-NSP8 complex through hydrophobic effects, leading to increased viral RdRp activity. Furthermore, competitive transmissibility assay reveals that reverse genetic (RG)-P323L or RG-P323L/G671S NSP12 outcompetes RG-WT (wild-type) NSP12 for replication in the upper respiratory tract, allowing markedly rapid transmissibility. This suggests that NSP12 P323L or P323L/G671S mutation of SARS-CoV-2 is associated with increased RdRp complex stability and enzymatic activity, promoting efficient transmissibility.
CRIS-Team Scopus Importer:2023-09-15
Keywords: CP: Immunology; ferret; NSP12 mutation; RNA-dependent RNA polymerase; SARS-CoV-2; transmissibility